Pemetaan Kinerja Pendapatan Asli Daerah dan Kemampuan Keuangan Daerah Kabupaten/Kota di Provinsi Nusa Tenggara Barat Tahun 2018-2022 - nabilah, nabilah; Hailuddin, Hailuddin; S, I Dewa Ketut Yudha (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study uses financial ratio analysis of the Regional Revenue and Expenditure Budget to assess the financial capability of regions in funding autonomy. This descriptive research employs quantitative analysis methods. The analysis tools include Mapping and Analysis of Regional Financial Capability using the Quadrant Method, Local Revenue Effectiveness Ratio, Degree of Independence, Patterns of Relationships between Central and Local Governments, Degree of Regional Dependence, and Regional Financial Capability Mapping. The data used is secondary data regarding the Regional Revenue and Expenditure Budget for the fiscal years 2018-2022. The study results show: (1) North Lombok Regency is in quadrant I; (2) Most Regencies/Cities in West Nusa Tenggara are ineffective in terms of Local Revenue Effectiveness Ratio; (3) The Regional Independence Level is low, only reaching 14.93, indicating an instructive relationship pattern with the central government.